Politics, plurality and problemsheds: a strategic approach for reform of agricultural water resources management - Mollinga, P.P.; Meinzen-Dick, Ruth S.; Merrey, Douglas J. (2007)
Starting from the assessment that past efforts at reform in agricultural water management in developing countries have achieved very little, this article argues that a fundamental change is required in the approach to policy and institutional transformation if the present deadlock in the internalisation of ecological sustainability, human development/poverty alleviation and democratic governance into the 'core business' of water bureaucracies is to be overcome. 'Social engineering' approaches need to be replaced by 'strategic action' approaches that acknowledge the inherently political character and the plurality of actors, institutions and objectives of water management - a perspective operationalised here around the notions of 'problemshed' and 'issue network.'